UPAYA UMAT BERAGAMA DALAM MENCEGAH GERAKAN RADIKAL MELALUI PENGUATAN EKONOMI (Studi di Desa Banjaroya Kalibawang Kulonprogo Yogyakarta) - A. Sihabul Millah (AN NUR: Jurnal Studi Islam, 2012)
This article tries to describe the result of research on strategies which are done by Muslim and Catholic groups in anticipating a religious radical movement in the Village of Banjaroya, sub- district of Kalibawang Kulonprogo, Yogyakarta. The result of research shows that the effort of religious community in preventing radical movement is by way of strengthening the community economy. This is done by identifying natural resources, concrete action of economic development, the establishment of rural financial institutions, and the establishment of a local economic development forum (LED). And the supporting factors of economic strengthening activity are the harmony of cultural and religious values and the equality of descent relationship among religious people.